Sustainable Reduction of Soil Permeability through Microbial Bio-Clogging - Viroon Kamchoom; Sumetha Chaisarn; Thiti Khattiwong; Laemthong Laokhongthavorn (Advances in science and technology, 2026)
Microbially induced bio-clogging presents a promising, sustainable alternative to conventional soil improvmeent methods for mitigating seepage in geotechnical applications. Despite its potential, uncertainties remain regarding the influence of bacterial concentration, culture medium application, and associated setting times under field-like conditions—factors which are critical to the effective deployment of this technology in practice. This study investigates the impact of bacterial bio-clogging on the hydraulic behaviour of coarse-grained soils, with particular emphasis on the system's performance during and following the cessation of culture medium supply. Laboratory experiments were conducted to assess the mechanisms of permeability reduction resulting from microbial colonisation and extracellular polymeric substance (EPS) production. Results demonstrate that bacterial adhesion and subsequent EPS accumulation lead to the progressive clogging of soil pores, causing a marked decline in saturated permeability. The observed reductions in permeability are comparable to those produced by traditional methods such as cement and bentonite grouting. This highlights the durability of the biofilm matrix and its ability to maintain hydraulic resistance in the absence of continued nutrient input. These findings contribute valuable insight into the viability of bio-clogging as a ground improvement strategy. By elucidating the relationship between bacterial activity, EPS production, and soil pore occlusion, this research advances the practical understanding required to optimise bio-mediated techniques for field-scale applications in sustainable geotechnical engineering.
Keywords: Microbial Applications in Construction Materials; Grouting, Rheology, and Soil Mechanics; Bacterial biofilms and quorum sensing